2020
DOI: 10.1177/2058739220967767
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin improves the survival in endotoxic mice and inhibits the inflammatory responses in LPS-treated RAW 264.7 macrophages

Abstract: Introduction: Sepsis is a severe disease with a high morbidity and mortality. Baicalin, an active compound of Chinese medicine, Scutellaria baicalensis Georgi (Huang Qui), exhibits several beneficial effects. In this study, we examined whether administration of baicalin increases the survival in mice with endotoxemia and investigated its anti-inflammatory mechanisms in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. Methods: The production of NOx, PGE2, and pro-inflammatory cytokines, the mRNA and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…This value is between 1.61 × 10 4 and 1.87 × 10 4 V/m, showing an intermediate state between the LPS activation and RAW 264.7 cells (Figure 3). This result is consistent with the alleviation function of the medicine recorded in previous literature [44]. The first five type of gates captured 68.4% of the cells, which are more likely to be LPS-activated cells.…”
Section: Label-free Device Can Detect Anti-inflammatory Medicinesupporting
confidence: 91%
See 2 more Smart Citations
“…This value is between 1.61 × 10 4 and 1.87 × 10 4 V/m, showing an intermediate state between the LPS activation and RAW 264.7 cells (Figure 3). This result is consistent with the alleviation function of the medicine recorded in previous literature [44]. The first five type of gates captured 68.4% of the cells, which are more likely to be LPS-activated cells.…”
Section: Label-free Device Can Detect Anti-inflammatory Medicinesupporting
confidence: 91%
“…Baicalin was recorded to alleviate the activation of LPS‐induced inflammation effectively and this effect could be detected by the device (Figure 2B) [44]. In the presence of 0.1 µg/mL LPS, 50 µM baicalin was used to treat activated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Park et al [58] reported that ginsenoside Rb1 exhibited NO inhibitory activity with an IC 50 value > 0.05 mM, similar to the results of the present study. Moreover, Kuo et al [59] indicated that 0.1 µg/mL LPS induced NO generation, which was dose-dependently inhibited by baicalin (10-50 µM). Similarly, we observed that baicalin elicited NO inhibitory activity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%